Whispers at moonrise - Hunter, C. C. (Hunter, C. C. Shadow Falls novel., 2012)
Even at a camp for supernatural teens, Kylie Galen has never been normal. Not only can she see ghosts but she doesn't seem to belong to any one species, instead she exhibits traits from them all. Her boyfriend Lucas, seems to be having problems accepting her for what she is and what she isn't. With his werewolf pack standing in the way, Kylie finds herself turning to Derek who seems willing to accept the impossible. As if life isn't hard enough, she starts getting visits from the ghost of Holiday, but Holiday isn't dead yet.